Expression of a cloned Staphylococcus aureus alpha-hemolysin determinant in Bacillus subtilis and Staphylococcus aureus - FOSTER, TIMOTHY (My University, 1983)
A DNA sequence encoding Staphylococcus aureus alpha-hemolysin, which had been previously cloned and mapped in Escherichia coli K-12, was introduced into Bacillus subtilis BD170 and several strains of S. aureus by using plasmid vectors, some of which could replicate in all three organisms. The determinant was cloned on a 3.3-kilobase pair DNA fragment into B. subtilis by using the vector plasmid pXZ105 to form the hybrid plasmid pXZ111. B. subtilis cells harboring pXZ111 produced large zones of alpha-hemolysis after 18 h of growth at 37 degrees C on rabbit blood agar plates, and alpha-hemolysin activity was detected in supernatants prepared from growing cultures of this strain. The alpha-hemolysin was apparently secreted across the B. subtilis cell envelope. Polypeptides of molecular weights 34,000 and 33,000 were precipitated with anti-alpha-hemolysin serum from lysates prepared from BD170 cells harboring pXZ111. A hybrid replicon which could replicate in both E. coli and S. aureus was constructed in E. coli by ligating a HindIII fragment encoding the replication functions and chloramphenicol resistance genes of S. aureus plasmid pCW59 to the pBR322 alpha-hemolysin hybrid plasmid pDU1150. The DNA of this plasmid, pDU1212, was prepared in E. coli and used to transform protoplasts prepared from a non-alpha-hemolytic, nonrestricting strain of S. aureus RN4220. Some of the transformants contained plasmids which had suffered extensive deletions. Some plasmids, however, were transformed intact into RN4220. Such plasmids were subsequently maintained in a stable manner. pDU1212 DNA was prepared from RN4220 and transformed into alpha-hemolytic S. aureus 8325-4 and two mutant derivatives defective in alpha-hemolysin synthesis. All three strains expressed alpha-hemolysin when harboring pDU1212.